Crowdsourcing : Tools for Viral Marketing : Phenomenological studies #anysongchallenge on Tiktok online platform - Risa Dwi Ayuni (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2022)
Tiktok is no longer new as Digital Marketing platform. By offering the convenience of creating content without involving video editing applications, it makes users more able to create their interests only with a mobile phone. Massively developed communication technology allows consumers to actively participate in various business activities. Not only relying on companies, but many other collaborative methods, one of which is crowdsourcing. The development of social media has facilitated the rapid development of crowdsourcing as an innovative tool in the field of marketing. One of the cases discussed in this phenomenological study is a song called Anysong by a South Korean singer named Zico. Using phenomenology, it shows that crowdsourcing, that empower the power of internet crowd, has massive effects as innovation in promotion.